Privacy in Early Modern Egodocuments : Personal Lives in Historical Perspective - Green, Michael; Kowalcze-Pawlik, Anna; Orzeł, Joanna (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
In early modern Europe, literacy was on the rise, and it became possible to reflect on one's own life and secrets in private notes, letters to family and friends, as well as dairies, memoirs, and travelogues. Privacy in Early Modern Egodocuments: Personal Lives in Historical Perspective combines historical research with an analysis of personal narratives from Eastern, Central, and Western Europe (also in the global context) to discuss what privacy meant at a time of political and social turmoil. The contributions explore personal writing by elite figures, as well as non-elite groups and marginalised voices, in a detective-like fashion, bringing into focus narratives that have long been overlooked in traditional historical studies. The authors offer insights into the evolution of the concept of privacy as well as the use of egodocuments as a vital resource for understanding individual and collective memory, particularly as shaped by the region's dynamic history. Contributors are: Andras Bandi, Jakub Basista, Michael Green, Nere Jone Intxaustegi Jauregi, Anna Kowalcze-Pawlik, Katarzyna Kuras, Bernadetta Manyś, Joanna Orzeł, François-Joseph Ruggiu, Robert T. Tomczak, Nataliia Voloshkova, and Aleksandra Ziober.